The Relation of Leadership and Communication to Work Climate and Its Effects on Employee Morale at National Civil Service Agency (BKN) Regional Office XII Pekanbaru - Merinta Fiona; Susi Hendriani; Yulia Efni (INTERNATIONAL JOURNAL OF ECONOMICS, BUSINESS AND APPLICATIONS, 2018)
The purpose of this study  was to determine the relation of leadership, communication to work climate and its effect on employees morale in National Civil Agency(BKN) Regional XII Pekanbaru partialy or joinly.The population of this study were all employeesof the National Civil Service Agency (BKN) Regional Office XII Pekanbaru totaling 94 employees.But based on job analysis in 2015 the ideal number of employees of each regional office is 90 employees. How to determine the number of samples by using the census method, so the sample number are 90 employees. Data analysis using Partial Least Square (PLS).The result of this study indicate that leadership and communication have a significant effect part to employees morale, but leadership through work climate does not have a significant effect on employees morale, and communication through work climate also have a significant effect to employees morale at the National Civil Service Agency (BKN) Regional Office XII Pekanbaru.